AN EXAMINATION OF ZAKAT INSTITUTIONS' LEVEL OF PRODUCTIVITY BEFORE AND FOLLOWING THE COVID-19 PANDEMIC - Ardiani, Ninda (Antis-publisher, 2024)
This study aims to analyze the productivity of zakat institutions in Indonesia before and during the COVID-19 pandemic. The potential of zakat in Indonesia is quite large, but in terms of channeling it is still not optimal. The lack of standardization in the management of zakat has resulted in inappropriate collection and distribution of zakat. Whether or not the zakat institution is optimal in carrying out its operational activities can be seen from the productivity of the zakat institution. One of the methods that can be used to analyze performance efficiency is by using the non-parametric Malmquist Productivity Index (MPI) method. The Zakat Institution which is the object of the research shows fluctuations in productivity in each research period. The period during the pandemic has more value than before the pandemic. During the COVID-19 pandemic, LazisMu showed excellent development in terms of productivity.